2014
DOI: 10.1007/978-3-319-07046-9_25
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Combinatorial Optimization with Decision Diagrams

Abstract: Abstract. We propose a new approach for parallelizing search for combinatorial optimization that is based on a recursive application of approximate Decision Diagrams. This generic scheme can, in principle, be applied to any combinatorial optimization problem for which a decision diagram representation is available. We consider the maximum independent set problem as a specific case study, and show how a recently proposed sequential branch-and-bound scheme based on approximate decision diagrams can be paralleliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…We will see that other families of graphs have properties which can interfere with this approach. Bergman et al (2014) used parallel decision diagrams, and showed excellent scalability-however, their sequential runtimes were typically much worse than state of the art algorithms.…”
Section: Parallel Branch and Bound And The Potential For Speedupmentioning
confidence: 99%
“…We will see that other families of graphs have properties which can interfere with this approach. Bergman et al (2014) used parallel decision diagrams, and showed excellent scalability-however, their sequential runtimes were typically much worse than state of the art algorithms.…”
Section: Parallel Branch and Bound And The Potential For Speedupmentioning
confidence: 99%
“…We then teamed up with Andersen and his student P. Tiedemann to propose a concept of relaxed MDDs, which we first applied to constraint programming but later became an essential tool for optimization [3]. Research on MDDs and optimization has moved in several directions since that time, including development of a general-purpose solver for discrete optimization [14,37], applications to nonlinear programming [10], and implementations with parallel processors [9]. Much of this research is described in a recent book [13] and conference [28].…”
Section: Decision Diagramsmentioning
confidence: 99%
“…Much more recently, Bergman et al (2014) worked on decision diagram search trees. When decision diagrams become too wide, usually a number of subproblems are created and evaluated sequentially.…”
Section: Richer Search Treesmentioning
confidence: 99%